Penerapan Model Pembelajaran Make a Match Untuk Meningkatkan Hasil Belajar Siswa - Mahfudz, Fadlan; Hajerah, Hajerah; Rostiah, Rostiah (Pinisi Journal Pendidikan Guru Sekolah Dasar, 2024)
The problem in this research is the low learning outcomes of Class V students. This research is classroom action research (PTK) which aims to determine the process of implementing the make a match model regarding human interaction for Class V students and to determine the increase in learning outcomes regarding student human interaction. Class V applies the make a match type cooperative learning model. The approach used in this study is a qualitative approach. The research subjects were the class teacher and students totaling 30 students, consisting of 13 male students and 17 female students. The research was carried out in two cycles. In cycle I, the results of research on the learning process were in good qualifications (B) and the average score of student evaluation test results was 60 with learning completeness not yet reaching ≥76%. Meanwhile, in cycle II, the results of research on the learning process were in good qualifications (B) and the average score of student evaluation test results was 72 with learning completion reaching ≥76%. The conclusion of this research is that the application of the make a match type cooperative learning model can improve student learning processes and outcomes regarding human interaction in Class V of SD Inpres Lekbeng.